High-Definition Transcranial Direct Current with Electrical Theta Burst on Post-Stroke Motor Rehabilitation: A Pilot Randomized Controlled Trial. (September 2022) - Huang, Yi-Jing; Wang, Shun-Min; Chen, Chieh; Chen, Chien-An; Wu, Chun-Wei; Chen, Jia-Jin; Peng, Chih-Wei; Lin, Che-Wei; Huang, Shih-Wei; Chen, Shih-Ching
Background: High-definition transcranial electrical theta burst superimposing direct current stimulation (HD-tDCS-eTBS) not only incorporates the therapeutic advantages of tDCS and TBS but enhances stimulation focality and practicality. However, the applicability of this innovative neuromodulatory device in post-stroke rehabilitation remains uncertain. Objective: This study aimed to assess the efficacy and safety of the HD-tDCS-eTBS on upper extremity (UE) motor function in patients with chronic stroke. Methods: A patient-blinded, randomized controlled study was conducted. Twenty-four participants were randomly assigned into either the active HD-tDCS-eTBS group or sham HD-tDCS-eTBS group. Both groups received 20 minutes of active/sham HD-tDCS-eTBS combined with 30 minutes of conventional UE rehabilitation each time, 3 times a week for 4 weeks. Outcome measures including the Fugl-Meyer Assessment of Upper Extremity, Wolf Motor Function Test, Jebsen-Taylor Hand Function Test, Finger-Nose Test, and Modified Ashworth Scale were assessed before and immediately after the intervention period. Results: Spasticity of shoulder adductor ( P  = .05), elbow extensor ( P  = .04), and thumb flexor ( P  < .01) were significantly reduced in the active HD-tDCS-eTBS group versus the sham group. Nonsignificant trends in the improvements of most other outcome measures were in favor of the active HD-tDCS-eTBS group with moderate to large effect sizes ( P  = .06–.26, η p 2  = 0.06–0.16). No severe adverse events except for slight skin redness under the stimulus electrode was detected after the HD-tDCS-eTBS. Conclusions: Our findings support that HD-tDCS-eTBS is safe and has therapeutic potential for post-stroke UE motor rehabilitation. Trial registration: ClinicalTrials.gov (ID: NCT04278105).